The sound power of a circular membrane for axially-symmetric vibrations - RDZANEK, W.; WITKOWSKI, P. (Archives of Acoustics, 1992)
This paper gives an analysis of the sound power with regard to the influence of a radiated wave on the vibrations of a membrane. The vibrations of the membrane are forces by time-harmonic external pressure. The source is placed in a rigid plannar baffle and radiates into a lossless and homogeneous gas medium. Distributing a velocity in a series of eigenfunctions, we could transform a motion equation into an algebraic system of linear equations. As the final result of the analysis, a relative real power of self and free vibrations for high frequency was derived using an approximate method. The expressions derived here are very useful and convenient for numerical calculations.